O Insituto do Amicus Curiae no controle de consitucionalide brasileiro: uma abordagem à luz da efetividade do princípio do acesso à justiça - Rocha, Anna Emanuella Nelson dos Santos Cavalcanti da (2008)
It presents a study about the control of constitutionality, its requirements and beddings. It brings, at first, notions about the concept of constitution, in its most varied aspects, as well as the systems of Control of Constitutionality. It emphasizes, considering the actual Brazilian situation, which passes through constitutional reforms and, therefore, assenting the appearance of an enormous amount of ordinary laws, the legal instability that has formed itself within the national panoram. Because of this situation, the institute of the Control of Constitutionality gains inmportancy as a way of protection of our Great Letter, against possible violations which can unfortunately happen. More ahead in the difuse control of constitutionality argues the new trend of generalization, especially after the recent reform that introduced the general repercussion as new requirement of admissibilidade of the appeal to the Brazilian Supreme Court. In the final chapter brings an analysis on the institute of amicus curiae, arguing its historical origins and its evolution, in the comparative jurisprudence, and the Brazilian right. From then is gone deep the paper of amicus curiae in the constitutionality control and, after quarrel on the difficulties of the Brazilian population to materialize its right before the judiciary, as this new institute could contribute in basic way for the materialization of the constitutional rule of access to justice